Alteration in miRNAs expression in paediatric acute lymphocyticleukaemia: Insight into patients' therapeutic response. (15th August 2020) - El‐maadawy, Eman A.; Bakry, Rania M.; Moussa, Mohamed M.; El‐Naby, SobhyHasab; Talaat, Roba M.
Abstract: MicroRNAs (miRNAs) revealed themselves as potential tumour markers and play a significant role in the pathogenesis and progression of acute lymphocytic leukaemia (ALL). This work is designed to investigate the expression of miR‐21, miR‐26, miR‐148a, miR‐133b and miR‐24 in paediatric ALL patients in response to treatment. The expression of miRNAs was determined by quantitative reverse transcriptase–polymerase chain reaction (qRT–‐PCR) in 43 paediatric ALL patients (33 treatment responders and 10 non‐responders) compared to 42 healthy controls. miR‐21, miR‐148a, and miR‐24 were found to be significantly ( P  < .05, P  < .01, P  < .05; respectively) up‐regulated in ALL patients compared to controls. No statistically significant differences in expression levels of miR‐26a and miR133b were detected in both groups. Concerning treatment, responders are found to have a decreased level of miR‐24 compared to non‐responder patients. A significant increase ( P  < .01) in miR‐24 expression level in relapsed patients compared to non‐relapsed ones was found. Positive correlations were detected between miR‐148a and miR‐24 ( r  = .347; P  < .05) and between miR‐26a and miR‐24 ( r  = .353; P  < .05) in ALL group. The highest sensitivity (72%) and specificity (81%) among miRNAs were detected in miR‐24 at a cut‐off value of 2.928. Taken together, the up‐regulation of tumour suppressor miRNA(miR‐148a) concur with the up‐regulation of oncomiR (miR‐21) might provide a new era that could help in disease management strategy. The reduction of oncomiR‐24 is one of the promising effects of treatment. A larger prospective study is highly recommended to confirm our findings. Abstract : This work is designed to investigate the expression of oncomiR (miR‐21), tumour suppression (miR‐26, miR‐148a, miR‐133b) and duel function miRNAs (miR‐24) in treated paediatric ALL patients. Our results revealed that miR‐21, miR‐148a, and miR‐24 were found to be significantly up‐regulated in ALL patients compared to controls. Responders to treatment are found to have elevated levels of miR‐148a and miR‐133b and low levels of miR‐21, miR‐24 and miR‐26a compared to non‐responder patients. Our data might provide a new era that could help in disease management strategy.